The effect of educational exercises using a self-regulated learning strategy on learning the performance phases of the triple jump activity for female students - Yahya, Diana Ghanem; Katea, Aseel Jalil (Indonesian Journal of Physical Education and Sport Science, 2026)
Studi purpose. This study seeks to explore how educational tasks performed by self-regulated learning strategy can be used to master the stages of the triple jump among physical education students of the female gender. The research is dealing with the performance variability in these technical stages and aims at improving learning efficiency in a quantitative and qualitative way. Materials and Methods. The experimenters used a sample size of 24 second-stage female students (Section A), half of them experimental (n=12) and half of them control (n=12). The experimental group completed a 6-week program with the use of the self-regulated learning method, which implied two instructional units per week. Evaluation was done according to the stages of the triple jump. Results. Evaluations at the end of the post-test showed that the technical performance of the triple jump phases of experimental and control groups significantly improved. The evidence indicates that self-regulated policy enabled students to internalize the motor skills enhancing the jump sequences better. Conclusions. The paper concludes that self-regulated learning based educational exercises have a specific positive impact on learning to triple jump. This plan is more effective than the conventional ones in minimizing the performance variation and hastening the learning of skills among female learners.